Comparison of Clinical Foetal Weight and Ultrasonography Detected Foetal Weight (Journal of Current and Advance Medical Research, 2019)
Background: Comparison of foetal weight detection between clinical examination and ultrasonography is very important. Objective: The purpose of the present study was to compare the detection of foetal weight between clinical examination and ultrasonography.Methodology: This cross-sectional comparative study was carried out in the Department of Obstetrics & Gynaecology at Rajshahi Medical Hospital Hospital (RMCH), Rajshahi, Bangladesh from July 2012 to June 2014 for a period of 2(two) years. Pregnant women with known gestational age at term (38 to 40 weeks of pregnancy), singleton pregnancy with longitudinal lie were included in this study. The clinical estimation of foetal weight was done. Foetal weight was estimated by using Johnson’s formula. The patient was then taken to Dept. of Radiology & Imaging, RMCH. Ultrasonographic estimation of foetal weight was done from estimation of foetal abdominal circumference (AC), biparietal diameter (BPD) and foetal femur length (FL). All the weights measured by ultrasound were recorded in the data sheet.Result: A total number of 245 pregnant women in term pregnancy were recruited as per inclusion and exclusion criteria. Table 1 shows age distribution of the study subjects. The mean age was 26.42 (SD ± 4.46). Low birth weight was found 12(4.9%) cases in ultrasonographic examination and 14(5.7%) cases in clinical measurement. Overweight was found 13(5.2%) cases in ultrasonographic examination and 16(6.5%) cases in clinical measurement. The mean with SD of birth weight among the study population were 3283.27±461.05 gram and 2870.41±424.84 gram in clinical and Ultrasonographic examination respectively (p < 0.05).Conclusion: In conclusion clinical estimation of foetal weight is significant differed with the measurement of USG.Journal of Current and Advance Medical Research 2019;6(2):92-96